2014
DOI: 10.1063/1.4863351
|View full text |Cite
|
Sign up to set email alerts
|

The structure of PX3 (X = Cl, Br, I) molecular liquids from X-ray diffraction, molecular dynamics simulations, and reverse Monte Carlo modeling

Abstract: Synchrotron X-ray diffraction measurements have been conducted on liquid phosphorus trichloride, tribromide and triiodide. Molecular Dynamics simulations for these molecular liquids were performed with a dual purpose: (1) to establish whether existing intermolecular potential functions can provide a picture that is consistent with diffraction data; (2) to generate reliable starting configurations for subsequent Reverse Monte Carlo modelling. Structural models (i.e., sets of coordinates of thousands of atoms) t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…In the previous sections, computational methods have been introduced whose results (including RDF, PRDFs, or total scattering function) depend on the applied set of interparticle potentials. In this subsection, a simulation method is introduced that is biased by the agreement with the measured diffraction data and that has been quite extensively applied for liquids consisting of tetrahedral molecules over the past nearly 20 years. , …”
Section: Computational Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the previous sections, computational methods have been introduced whose results (including RDF, PRDFs, or total scattering function) depend on the applied set of interparticle potentials. In this subsection, a simulation method is introduced that is biased by the agreement with the measured diffraction data and that has been quite extensively applied for liquids consisting of tetrahedral molecules over the past nearly 20 years. , …”
Section: Computational Methodsmentioning
confidence: 99%
“…It was found that both the neutron and the X-ray diffraction data were reproduced at a nearly quantitative level by the MD simulation that applied the OPLS all-atom force field, see Figure 2 of ref . (Note that this is not true for the hard-sphere reference system, for which significant deviations were detected from both sets of experimental data, see again Figure 2 of ref .) The RMC calculation that followed the MD simulation acted as a refinement to the MD configuration and was able to achieve a perfect fit to both X-ray and neutron diffraction data.…”
Section: Liquids Of Nearly Tetrahedral Moleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…For 3D-visualization of particle configurations compatible with our experimentally observed scattered intensities, a reverse Monte Carlo (RMC) algorithm was applied to I(q). [39][40][41][42] It is based on the experimental size distribution of spheres, and calculation of I(q) of homogeneous interacting polydisperse spheres with an excluded volume. 43 The basic design of the algorithm is outlined in ref.…”
Section: Methodsmentioning
confidence: 99%